The Development of Social Services in the Perspective of Welfare Pluralism - Dunajevas, Eugenijus (Sociologija. Mintis ir veiksmas, 2009)
The aim of this article is to show transformations of social services (social security, health care, education, social care and social work) in the perspective of welfare pluralism. The analysis shows that the development of social services in Western capitalist countries went through three different stages. In the first stage the major provider of social services was voluntary sector (NGO) and only at the end of eighteenth century public social services were established. The rapid growth and extension of publically provided social services in Western societies started after World War II. This period of social services development is characterized by the tendency to transfer the responsibility for social risks from private to public realm and is called the golden age of the welfare state. Since the end of 1970s the conception of welfare state undergoes sharp critique in Western democratic countries. The article claims that the new type of social services system, radically different from the postwar welfare state, is emerging.
Keywords: welfare state; welfare pluralism; social services; social policy; public management reform